Evidence-based training in professional music therapy: a model for tertiary educators. Issue 1 (1st June 2016) - Heiderscheit, Annie; Short, Alison
Abstract : Background : Across health-care education, practitioners are expected to engage in evidence-based practice. Students are taught to find and use credible evidence. Educators also need to consider evidence about teaching practices and how to best teach music therapy knowledge and skills. Scant evidence exists in this area. Objective : This paper explores evidence-based teaching practices in music therapy training programs to understand existing knowledge in both music therapy and related fields. Methods : A literature review determining existing knowledge, followed by an email survey of international and European music therapy programs provides evidence of existing practices, fostering the development of a proposed model for future development. Discussion : To provide best quality training in the music therapy profession, evidenced-based practice needs to be addressed in teaching students to find clinical information, but also by teachers to implement teaching methods and approaches for optimal learning. Educators need to understand levels of evidence related to teaching. A proposed model for future development provides guidelines for teaching practice. Conclusions : Addressing evidence-based teaching practices strengthens the training of professional music therapists.